A tale of two MENAs - Abdelaziz, Fatma; Breisinger, Clemens (Kiel Institute for the World Economy, 2018)
While conflict hinders growth in One MENA, GDP growth in the Other MENA is depressed by the effect of neighbouring conflicts and fluctuating oil prices. Thus economic growth rates are too low to cause a swift reduction in youth unemployment. A breakthrough could occur if MENA countries not affected by conflict achieved pursued reforms and achieved significant increments in GDP. Other MENA countries should implement structural reforms that attract FDI and that encourage export-led growth that can boost employment prospects for both locals and refugees. The international community should increase its support to Other MENA countries, including those that are hosting refugees.